2022
DOI: 10.5312/wjo.v13.i4.381
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive outpatient management of iliopsoas muscle abscess in complicated spondylodiscitis

Abstract: BACKGROUND Iliopsoas muscle abscess (IPA) and spondylodiscitis are two clinical conditions often related to atypical presentation and challenging management. They are both frequently related to underlying conditions, such as immunosuppression, and in many cases they are combined. IPA can be primary due to the hematogenous spread of a microorganism to the muscle or secondary from a direct expansion of an inflammatory process, including spondylodiscitis. Computed tomography-guided percutaneous drain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Only 190 patients had their gender described, and 103 males and 87 females were evaluated at a mean follow-up of 23.5 months. Twelve studies used CT-guided PD [ 21 , 22 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], seven studies used US-guided PD [ 12 , 36 , 37 , 38 , 39 , 40 , 41 ], and two studies used both CT-guided and US-guided PD [ 42 , 43 ] ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only 190 patients had their gender described, and 103 males and 87 females were evaluated at a mean follow-up of 23.5 months. Twelve studies used CT-guided PD [ 21 , 22 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], seven studies used US-guided PD [ 12 , 36 , 37 , 38 , 39 , 40 , 41 ], and two studies used both CT-guided and US-guided PD [ 42 , 43 ] ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…A review of 20 articles found that 12 articles focused on CT-guided PD [ 21 , 22 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. These studies were all retrospective, and a total of 181 patients were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations